STUDI LAPANGAN REHABILITASI DAN REKONTRUKSI OLEH BPBD PROVINSI LAMPUNG PASCA BENCANA TSUNAMI SELAT SUNDA TAHUN 2018 - M Maryanti; Diane Tanti Poli; Admiral Musa Julius; Andi Ahmad Aminullah; Andi Windra Sandi (Jurnal Manajemen Bencana (JMB), 2020)
The Agency for Meteorology, Climatology, and Geophysics of Indonesia (BMKG) has declared  tsunami was happened in December 22th 2018 that affected Lampung Province, especially in South Lampung area. This tsunami caused by lanslide under the sea after Krakatau mountain eruption. Based on the affects from tsunami in Sunda Strait in South Lampung, The Agency for Disaster Management of Lampung (BPBD) arranged the plan for rehabilition and recontruction appropriate with rules from The  National Agency for Disaster Management (BNPB) Number 5 2017. Rehabilitation and Recontruction divided into six aspects, there are Humanity, Housing, infrastructure, Economic, Social, and across sectors. The financial source for the process is from Indonesian State Budget (APBN). All of the process is an implementation of sinergy among BPBD Lampung, BNPB, and Indonesian Government.